2012
DOI: 10.21273/hortsci.47.8.1171
|View full text |Cite
|
Sign up to set email alerts
|

Glycinebetaine Seed Priming Improved Osmotic and Salinity Tolerance in Turfgrasses

Abstract: Exogenous application of glycinebetaine (GB), an osmoprotectant, increases tolerance to stresses including salinity in various plants. Information on turfgrass, however, is limited. In this study, GB was used to prime turfgrass seeds to enhance salinity tolerance during germination and seedling growth stage when plants are more sensitive to stresses. Unprimed and primed (50, 100, 150, or 200 mm solution of GB or distilled water) seeds of perennial ryegrass (Lolium perenn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Therefore, no standard methods to treat seeds or target osmotic or ionic effects of salt stress are clearly defined. For example, seed priming with glycine betaine resulted in enhanced seed germination and seedling growth of turfgrasses under salinity (Zhang & Rue, ), while NaCl in hot pepper ( Capsicum annuum L.) was the most effective treatment to improve seed performance under normal as well as under saline conditions (Amjad et al., ; Khan et al., ). In maize ( Zea mays L.), different salts used as priming agents were effective in alleviating adverse effects of salt stress at germination stage (Ashraf & Rauf, ), and similar results were reported for fine aromatic rice (Afzal et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, no standard methods to treat seeds or target osmotic or ionic effects of salt stress are clearly defined. For example, seed priming with glycine betaine resulted in enhanced seed germination and seedling growth of turfgrasses under salinity (Zhang & Rue, ), while NaCl in hot pepper ( Capsicum annuum L.) was the most effective treatment to improve seed performance under normal as well as under saline conditions (Amjad et al., ; Khan et al., ). In maize ( Zea mays L.), different salts used as priming agents were effective in alleviating adverse effects of salt stress at germination stage (Ashraf & Rauf, ), and similar results were reported for fine aromatic rice (Afzal et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, no standard methods to treat seeds or target osmotic or ionic effects of salt stress are clearly defined. For example, seed priming with glycine betaine resulted in enhanced seed germination and seedling growth of turfgrasses under salinity (Zhang & Rue, 2012), while NaCl in hot pepper (Capsicum annuum L.)…”
Section: Discussionmentioning
confidence: 99%
“…Thus, soaking seeds in ascorbate, salicylic acid, kinetin and CaCl 2 for 12 h resulted in a high salt stress tolerance in wheat plants, with increments in K accumulation and reductions in Na content in their leaves [75]. Also, a decreased NaCl toxicity was observed after priming turfgrass seeds with glycine betaine [76] or after the osmopriming with PEG-6000 in sorghum seeds, demonstrating a palliative effect even in low quality seeds [77].…”
Section: Effect Of Seed Priming On Ion Homeostasis To Cope With Abiotmentioning
confidence: 95%
“…As a result, some of these substances might even be useful in seed priming treatments for abiotic stress alleviation. For instance, Zhang and Rue (2012) showed that seed priming with glycine betaine improved the osmotic and salinity tolerance of turfgrasses, resulting in enhanced seed germination and seedling growth under salinity stress. Oliveira et al (2011b) verified that the osmopriming of low physiological quality sorghum seeds (non-aged) reduced the negative effects of salinity (100 mM NaCl) on seedling growth.…”
Section: Figmentioning
confidence: 99%